Positive Solutions for a System of Hadamard-Type Fractional Differential Equations with Semipositone Nonlinearities - Youzheng Ding; Jiqiang Jiang; Donal O’Regan; Jiafa Xu (Complexity)
In this paper, we use the fixed-point index and nonnegative matrices to study the existence of positive solutions for a system of Hadamard-type fractional differential equations with semipositone nonlinearities.